Severe Neurodevelopmental Impairment in Neonates Born Preterm: Impact of Varying Definitions in a Canadian Cohort - Haslam, Matthew D.; Lisonkova, Sarka; Creighton, Dianne; Church, Paige; Yang, Junmin; Shah, Prakesh S.; Joseph, K.S.; Synnes, Anne; Harrison, Adele; Ting, Joseph; Cieslak, Zenon; Sherlock, Rebecca; et al. (The Journal of pediatrics, 2018)
To assess the impact of variations in the definition of severe neurodevelopmental impairment (NDI) on the incidence of severe NDI and the association with risk factors using the Canadian Neonatal Follow-Up Network cohort. Literature review of severe NDI definitions and application of these definitions were performed in this database cohort study. Infants born at 23-28 completed weeks of gestation between 2009 and 2011 (n = 2187) admitted to a Canadian Neonatal Network neonatal intensive care unit and assessed at 21 months' corrected age were included. The incidence of severe NDI, aORs, and 95% CIs were calculated to express the relationship between risk factors and severe NDI using the definitions with the highest and the lowest incidence rates of severe NDI. The incidence of severe NDI ranged from 3.5% to 14.9% (highest vs lowest rate ratio 4.29; 95% CI 3.37-5.47). The associations between risk factors and severe NDI varied depending on the definition used. Maternal ethnicity, employment status, antenatal corticosteroid treatment, and gestational age were not associated consistently with severe NDI. Although maternal substance use, sex, score of neonatal acute physiology >20, late-onset sepsis, bronchopulmonary dysplasia, and brain injury were consistently associated with severe NDI irrespective of definition, the strength of the associations varied. The definition of severe NDI significantly influences the incidence and the associations between risk factors and severe NDI. A standardized definition would facilitate site comparisons and scientific communication.